Preferensi Santri Putra pada BMT Sunan Drajat Paciran Di Pondok Pesantren Sunan Drajat Lamongan - Fatkhur Rouf; Muhammad Awaludin Islam; Musbikhin Musbikhin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
BMT Sunan Drajat is a sharia financial institution within the pesantren environment. Therefore, the preference of students for participating in saving at BMT Sunan Drajat needs to be taken into account. This study aims to find out how the preferences of students at BMT Sunan Drajat. While the research methodology uses a quantitative approach methodology with testing starting with theories or hypotheses using the chi square approach. The results of this study show that the calculated Chi Square value is 14.474. Because the Chi Square value is > 13.362, based on the basis for making the decision above, it can be concluded that H0 is rejected and Ha is accepted. Thus it can be interpreted in terms of facilities that male students have a good preference for BMT Sunan Drajat